Hubungan Antara Penggunaan Media Sosial dan Kecemasan Sosial pada Generasi Milenial - Rihyanti, Erni (LANCAH: Jurnal Inovasi dan Tren, 2023)
This study aims to investigate the relationship between social media use and social anxiety in the millennial generation. Using literature research methods and correlation analysis, we collected data from respondents representing this generation to explore the impact of the intensity of social media use on levels of social anxiety. The research results show that there is a significant negative relationship between social media use and social anxiety in the millennial generation. These findings provide further understanding of how social media can act as an alternative channel in reducing levels of social anxiety among this generation. However, it should be noted that this influence may be influenced by various contextual and psychological factors. The implications of this research include the potential to develop intervention strategies that support the mental well-being of the millennial generation through managing social media use. These conclusions make a positive contribution to our understanding of the complex dynamics between technology and psychological well-being, opening the door to further research in this area.